Discovery of non-retinoid compounds that suppress the pathogenic effects of misfolded rhodopsin in a mouse model of retinitis pigmentosa. - Joseph T Ortega; Jacklyn M Gallagher; Andrew G McKee; Yidan Tang; Miguel Carmena-Bargueňo; Maria Azam; Zaiddodine Pashandi; Marcin Golczak; Jens Meiler; Horacio Pérez-Sánchez; Jonathan P Schlebach; Beata Jastrzebska (PLoS Biology)
Pathogenic mutations that cause rhodopsin misfolding lead to a spectrum of currently untreatable blinding diseases collectively termed retinitis pigmentosa. Small molecules to correct rhodopsin misfolding are therefore urgently needed. In this study, we utilized virtual screening to search for drug-like molecules that bind to the orthosteric site of rod opsin and improve its folding and trafficking. We identified and validated the biological effects of 2 non-retinoid compounds with favorable pharmacological properties that cross the blood-retina barrier. These compounds reversibly bind to unliganded rod opsin, each with a Kd comparable to 9-cis-retinal and improve opsin stability. By improving the internal protein structure network (PSN), these rod opsin ligands also enhanced the plasma membrane expression of total 36 of 123 tested clinical RP variants, including the most prevalent P23H variant. Importantly, these compounds protected retinas against light-induced degeneration in mice vulnerable to bright light injury and prolonged survival of photoreceptors in a retinitis pigmentosa mouse model for rod opsin misfolding.